An Unusual Presentation of Plasma Cells – Castleman Disease: A Case Report - Mihăilă Mariana; Herlea V.; Dobrea Camelia; Lupescu Ioana; Munteanu Gina Rusu; Chiriac Grethi; Micu L.; Serescu R.; Copaci I. (Romanian Journal of Internal Medicine, 2016)
We present the case of a 76 year old female patient admitted in the Department of Cardiology for physical asthenia, profuse sweating and dyspnea with orthopnea for about one month. Clinical and paraclinical assessments performed at admission confirmed the diagnosis of cardiac tamponade. Surgical intervention was performed and 400 mL of clear effusion were drained. Post-operative evolution was marked by recurrence of symptoms, requiring after 3 weeks a new drainage of 600 mL of clear effusion, and biopsy of the pericardium was performed. Pathological exam described serous pericarditis with chronic inflammatory infiltrate, xanthogranulomatous reaction intricated in the pericardium and mesothelial hyperplasia. The patient was subsequently transferred to the Department of Internal Medicine for further investigations. Physical examination showed a patient with altered general status, pallor, vesicular murmur absent in both bases, presenting cutaneous hyperpigmentation at the level of the right hemi-abdomen and hip with posterior extension, and a peripheral indurated erythematous plaque. The patient presented nodular masses of 3 cm in the right latero-cervical and bilateral axillary regions, non-adherent to the superficial structures, as well as adenopathic blocks in both inguinal regions. CT scan of the thorax and abdomen showed moderate bilateral pleuresia, minimal pericardial effusion (15 mm) and multiple adenopathies on both sides of the diaphragm. Skin biopsy was performed, as well as bone marrow aspirate and excision of a right axillary lymph node. Pathological exams and immunohistochemistry tests confirmed the diagnosis of Plasma Cells Castleman disease.